1999
DOI: 10.1093/phr/114.5.448
|View full text |Cite
|
Sign up to set email alerts
|

Research article. Racial discrimination and alcohol-related behavior in urban transit operators: Findings from the San Francisco Muni Health and Safety Study

Abstract: Data from a sample of urban transit operators showed an association between the number of domains of discrimination and some alcohol-related outcomes, but not others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 27 publications
9
93
0
Order By: Relevance
“…First, the results add to the sparse evidence base suggesting that exposure to racial prejudice and discriminatory treatment is associated with heavy drinking and alcohol problems among Blacks and Latinos generally (Mulia et al, 2008;Richman et al, 1996;Yen et al, 1999aYen et al, , 1999b. Bivariate analyses showed an overall pattern of incremental increases in past-year drunkenness, any drinking consequences, and two or more dependence symptoms at increasing levels of both perceived racial stigma and perceived unfair treatment, although there were exceptions to this rule, and not all of the associations were signifi cant.…”
Section: Discussionmentioning
confidence: 75%
“…First, the results add to the sparse evidence base suggesting that exposure to racial prejudice and discriminatory treatment is associated with heavy drinking and alcohol problems among Blacks and Latinos generally (Mulia et al, 2008;Richman et al, 1996;Yen et al, 1999aYen et al, , 1999b. Bivariate analyses showed an overall pattern of incremental increases in past-year drunkenness, any drinking consequences, and two or more dependence symptoms at increasing levels of both perceived racial stigma and perceived unfair treatment, although there were exceptions to this rule, and not all of the associations were signifi cant.…”
Section: Discussionmentioning
confidence: 75%
“…These fi ndings extend prior research focused on racial discrimination and its negative impacts on minority drinking problems. Interestingly, although we used a broad measure of unfair treatment that differs from measures of racial discrimination used by Yen et al (1999) and Martin et al (2003), the observed associations with problem drinking are of similar magnitude across these studies, corresponding to a twofold increased risk in minority populations. This suggests that social hardship of this nature may have robust effects on problem drinking among black and Hispanic Americans.…”
Section: Discussionmentioning
confidence: 94%
“…The lack of a relationship between social disadvantage and at-risk drinking among drinkers was somewhat unexpected, given that several studies have reported a positive relationship to heavy drinking (Mulia, 2003;Yen et al, 1999;Zemore et al, 2006). However, the operationalization of heavy drinking has varied across studies, and the at-risk drinking measure used here applies relatively low cutpoints, consistent with NIAAA's clinician guidelines (NIAAA, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of studies have found that chronic exposure to racial bias and unfair treatment is associated with exces-sive alcohol use and problems (Chae et al, 2008b;Gee et al, 2007;Martin et al, 2003;Mulia et al, 2008b;Yen et al, 1999;Zemore et al, 2011). Research on these social adversities has been largely directed at understanding minority health and racial disparities in health rather than socioeconomic disparities per se.…”
Section: Social Adversity and Alcohol Problemsmentioning
confidence: 99%